Promoting students’ critical thinking and creativity through TPACK based flipped classroom learning model in higher education - Mustadi, Ali; Ghufron, Anik; Fakhrudin, Ali (Edelweiss Applied Science and Technology, 2024)
The rapid development of technology has influenced various aspects of life, including education. Optimal utilization of technology can be a crucial step in creating better education that is relevant to the demands of the digital era. One of the learning approaches considered relevant in this era is the flipped classroom model based on TPACK (Technological Pedagogical Content Knowledge). This model is believed to enhance critical and creative thinking skills, which are essential in facing the challenges of the digital age. This study aims to examine the effects of the flipped classroom model integrated with TPACK (FC-TPACK) on the critical thinking and creativity of prospective elementary school teachers. This study employed a pretest-posttest experimental design involving 250 students from public universities in Indonesia. The experimental group consisted of 125 students who used the FC-TPACK model, while the control group comprised 125 students who received conventional learning without FC-TPACK. Data analysis was conducted using MANOVA to assess the overall effect of the learning model, and ANOVA was used to examine differences in each aspect of critical thinking and creativity. The ANOVA results showed significant differences between the experimental and control groups in terms of critical thinking and creativity skills, with a significance value of 0.000 ≤ 0.05 for all aspects measured. The experimental group demonstrated significant improvements in analysis, evaluation, innovation, flexibility in thinking, and originality compared to the control group. Therefore, the FC-TPACK model is recommended for use in learning to support the development of essential skills in the digital era.